1989
DOI: 10.1152/jappl.1989.67.4.1371
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in lung expansion in rabbits: prone vs. supine positions

Abstract: We studied the vertical gradient in lung expansion in rabbits in the prone and supine body positions. Postmortem, we used videomicroscopy to measure the size of surface alveoli through transparent parietal pleural windows at dependent and nondependent sites separated in height by 2-3 cm at functional residual capacity (FRC). We compared the alveolar size measured in situ with that measured in the isolated lungs at different deflationary transpulmonary pressures to obtain transpulmonary pressure (pleural surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 0 publications
4
38
1
3
Order By: Relevance
“…The end-expiratory P1iq values from the present study are similar to those previously obtained in rabbits with intrapleural cannulae (Miserocchi et al 1982) and micropipettes (Miserocchi et al 1988a), yet they are significantly more negative than those obtained with the 'rib capsule' technique in the rabbit (Yang et al 1989 (Albertine, Wiener-Kronish, Bastacky & Staub, 1991) they are likely to occur on a functional basis (Grotberg & Glucksberg, 1994). In fact simultaneous measurements of Pliq and Pp1 (Miserocchi,Nakamura & Agostoni,198 la), indicate that the former is more subatmospheric than the latter at any height.…”
Section: Intercostal and Costal Tubes For Pliq Measurementsupporting
confidence: 89%
See 1 more Smart Citation
“…The end-expiratory P1iq values from the present study are similar to those previously obtained in rabbits with intrapleural cannulae (Miserocchi et al 1982) and micropipettes (Miserocchi et al 1988a), yet they are significantly more negative than those obtained with the 'rib capsule' technique in the rabbit (Yang et al 1989 (Albertine, Wiener-Kronish, Bastacky & Staub, 1991) they are likely to occur on a functional basis (Grotberg & Glucksberg, 1994). In fact simultaneous measurements of Pliq and Pp1 (Miserocchi,Nakamura & Agostoni,198 la), indicate that the former is more subatmospheric than the latter at any height.…”
Section: Intercostal and Costal Tubes For Pliq Measurementsupporting
confidence: 89%
“…Another non-invasive method, originally developed for larger animals, involves the use of capsules fixed to a rib through which holes are drilled (Wiener-Kronish, Gropper & Lai-Fook, 1985; Olson & Lai-Fook, 1988;Urmey, De Troyer, Kelly & Loring, 1988;Yang, Kaplowitz & Lai-Fook, 1989;Yang & Lai-Fook, 1991). This technique represented a major step forward since it allowed dynamic recording without being invasive, however, there was one major drawback: the potential lack of hydraulic continuity between the capsule and the pleural fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman and colleague (14,15) found a significant vertical gradient of air content (3.3% air/cm at functional residual capacity) in the supine position, but a minimal gradient (Ϫ0.36% air/cm) in the prone position. Other studies found similar gradients of subpleural alveolar size (44), pleural pressure (41), and alveolar volume by PET (38) in the supine position, but no or minimal gradient in the prone position.…”
Section: Repeatability Of Xe-ct Methodsmentioning
confidence: 65%
“…Em posição supina, o coração e as estruturas do mediastino repousam sobre as partes mediais dos lobos inferiores exercendo pressão em torno de 5 cmH 2 O.cm -2 em pacientes adultos sem doença cardíaca, e em torno de 7 a 8 cmH 2 O.cm -2 nos pacientes com lesão pulmonar aguda 27 . Nos pacientes submetidos à anestesia e ventilação mecâ-nica, é provável que a compressão mecânica das regiões pulmonares dependentes e caudais seja o fator mais importante para o colapso pulmonar observado no intra-operató-rio 26,28,29 . Estudando pacientes submetidos à operação abdominal sob anestesia geral por meio de tomografia computadorizada de tórax, Brismar e col. encontraram densidades pulmonares maiores nos segmentos mais caudais e menores nas regiões mais cefálicas 30 .…”
Section: Mecanismos Do Colapso Pulmonar Intra-operatóriounclassified
“…In the supine position, the heart and other mediastinal structures rest on the medial regions of the inferior lobes, exerting a 5 cmH 2 O.cm -2 pressure in adult patients without cardiac diseases, and approximately 7 to 8 cmH 2 O.cm -2 in patients with acute pulmonary lesion 27 . In anesthetized patients on mechanical ventilation, the mechanical compression of dependent and caudal lung regions is probably the most important factor in the development of intraoperative pulmonary collapse 26,28,29 . In a study by Brismar et al of patients undergoing abdominal surgery under general anesthesia, CT scan of the chest demonstrated pulmonary densities that were more pronounced in caudal regions than in the upper areas of the lungs 30 .…”
Section: Mechanisms Of Intraoperative Pulmonary Collapsementioning
confidence: 99%